TOPONYMS OF THE HARRY POTTER SERIES OF NOVELS AND THE BASIS OF THEIR ORIGIN (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
A toponym is the name of a natural or antropological territory on Earth, and in fiction toponyms are used not only to name the place being described, but also to give the place its first assessment, convey information about the landscape, hero or author, or to give the reader aesthetic pleasure. The place names used in the “Harry Potter” series have also been selected for their various purposes by conducting a genetical-gnoseological analysis on 4 of them.